2020
DOI: 10.1016/j.aninu.2020.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Live yeast supplementation during late gestation and lactation affects reproductive performance, colostrum and milk composition, blood biochemical and immunological parameters of sows

Abstract: This study was conducted to evaluate the effects of dietary live yeast (LY) supplementation during late gestation and lactation on reproductive performance, colostrum and milk composition, blood biochemical and immunological parameters of sows. A total of 40 multiparous sows were randomly fed either the control (CON) diet or the CON diet supplemented with LY at 1 g/kg from d 90 of gestation to weaning. Results showed that the number of stillborn piglets and low BW piglets were significantly decreased in the LY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 42 publications
8
15
0
1
Order By: Relevance
“…This might be related to an increase in HDL-C and LDL-C and a decrease in very-low-density lipoprotein. Excessive accumulation of serum enzymes, such as AST and ALP, usually indicates liver damage [ 47 ]. In this research, low-dose GP had no toxic damage to the liver, and there were other active substances (such as geniposide, organic acids, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…This might be related to an increase in HDL-C and LDL-C and a decrease in very-low-density lipoprotein. Excessive accumulation of serum enzymes, such as AST and ALP, usually indicates liver damage [ 47 ]. In this research, low-dose GP had no toxic damage to the liver, and there were other active substances (such as geniposide, organic acids, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…When the piglets ingest colostrum, they uptake these compounds and, as a result, improve their immunity. Live yeast and probiotics supplementation around the time of farrowing and during lactation have proven to show positive effects on colostrum quality [ 8 ], litter performance [ 9 ], or maintenance of body reserves. More specifically, Saccharomyces cerevisiae var.…”
Section: Introductionmentioning
confidence: 99%
“…Major products of dietary fiber fermentation are SCFAs (acetic acid, propionic acid, butyric acid, valeric acid, isobutyric acid, and isovaleric acid), which carry out diverse functional roles such as activating G-coupled-receptors, inhibiting histone deacetylases, and serving as energy substrates (31). Many studies have indicated that dietary fibers effectively alter intestinal microbiota composition and diversity in pregnant sows (9,11,21). Although in this study we failed to determine the intestinal microbial composition of sows, the results for fecal SCFAs may partially explain the regulation of dietary fiber on microbiota.…”
Section: Discussionmentioning
confidence: 67%
“…Many studies have highlighted the beneficial effects of a high fiber diet on the reproductive performance of sows (15)(16)(17)(18)(19)(20). Dietary supplementation with a by-product from R. puerariae is expected to improve the reproductive performance and shows beneficial effects on satiety and behavior as other fiber sources in sow (21).…”
Section: Discussionmentioning
confidence: 99%